Insect-Based Foods: A Preliminary Qualitative Study Exploring Factors Affecting Acceptance and New Product Development Ideas through Focus Groups - Leocardia Ranga; Francesco Noci; Maria Dermiki (Challenges)
While insect-based foods could contribute towards sustainable protein consumption and production, their successful adoption relies largely on consumer acceptance. This case study aims to explore factors affecting acceptance and to identify the insect-based foods that participants would like to be developed and introduced to the market. Three focus groups incorporating optional tasting sessions of insect-based foods were conducted in Ireland, a country where these foods were unavailable at the time of the study. Findings showed that before the tasting sessions, public opinion, portion size comparisons (insects vs. meat), and witnessing entomophagy-related disturbing experiences through television were some of the factors that negatively influenced acceptance. Lack of availability in Ireland was the main factor that hindered consumption among participants willing to consume these foods. Participants’ usual food choice motives, sensory attributes, and inclusion percentages of insects in food were some factors which affected acceptance following the tasting sessions. A variety of insect-based foods was suggested for product development, which were mostly components of a main meal. The findings of this study could give an initial indication of product ideas that could be explored further for product development in regions where insect-based foods are not readily available on the market. These findings could contribute to future studies that would aim to build quantitative tools.